Ser amórfica: uma autoexperiência de ódio ao corpo transformada em pesquisa e criação artística - Paiva, Marília Almeida (2024)
This autobiographical master's thesis is a reflective dive into the process of accepting the body of someone who suffers from Body Dysmorphic Disorder and has found an antidote in art. The artist and researcher shares her personal experience, intertwining it with a theoretical investigation into the cultural construction of body hatred, highlighting the incessant search for a body idealization that has been shaped throughout history. The work explores the impacts of these idealized constructions on body-related disorders, weaving a narrative and using the language of video art, photography and performance. The theoretical framework adopted includes Emily L. Newman (2016), David Le Breton (1999), Arlindo Machado (1995), Renato Cohen (2019), Philippe Dubois (2004) and Denise Bernuzzi (2014). Research carried out at the Laboratory for Research into the Body, Communication and Art-LICCA (UFC/DGE-CNPq).